Adenosine Amine Congener as a Cochlear Rescue Agent. (26th August 2014) - Vlajkovic, Srdjan M.; Chang, Hao; Paek, Song Yee; Chi, Howard H.-T.; Sreebhavan, Sreevalsan; Telang, Ravindra S.; Tingle, Malcolm; Housley, Gary D.; Thorne, Peter R.
Abstract : We have previously shown that adenosine amine congener (ADAC), a selective A1 adenosine receptor agonist, can ameliorate noise- and cisplatin-induced cochlear injury. Here we demonstrate the dose-dependent rescue effects of ADAC on noise-induced cochlear injury in a rat model and establish the time window for treatment. Methods . ADAC (25–300 μ g/kg) was administered intraperitoneally to Wistar rats (8–10 weeks old) at intervals (6–72 hours) after exposure to traumatic noise (8–16 kHz, 110 dB sound pressure level, 2 hours). Hearing sensitivity was assessed using auditory brainstem responses (ABR) before and 12 days after noise exposure. Pharmacokinetic studies investigated ADAC concentrations in plasma after systemic (intravenous) administration. Results . ADAC was most effective in the first 24 hours after noise exposure at doses > 50 μ g/kg, providing up to 21 dB protection (averaged across 8–28 kHz). Pharmacokinetic studies demonstrated a short (5 min) half-life of ADAC in plasma after intravenous administration without detection of degradation products. Conclusion . Our data show that ADAC mitigates noise-induced hearing loss in a dose- and time-dependent manner, but further studies are required to establish its translation as a clinical otological treatment.